ANGKA KEJADIAN DIARE PADA ANAK DENGAN LEUKEMIA LIMFOBLASTIK AKUT DI RSUP PROF. DR. R. D. KANDOU MANADO PERIODE TAHUN 2011-2015 - Latamu, Fatmawati; Manoppo, Jeanette I. Ch.; Mantik, Max F. J. (Universitas Sam Ratulangi, 2016)
ABSTRACTBackground : Leukemia is a type of non-transmitted disease that cause death with a large number of cases, especially in children. Leukemia is the most common childhood cancer. Acute Lymphoblastic Leukemia (ALL) is approximately 75% of all cases. One of the main consequences of leukemia is inability of the immune system defending the body from the invasion of foreign objects. As a result of infection or bleeding is the most common cause of death in patient with leukemia. Diarrhea is one of the infections that can be found in children with Acute Lymphoblastic Leukemia. Diarrhea in children with Acute Lymphoblastic Leukemia can occur either from the disease itself or due to chemotherapy. The purpose of this study is to describe the incidence of diarrhea in children with acute lymphoblastic leukemia in Prof. R. D. Kandou Hospital Manado year period 2011-2015.Methods : This study is a descriptive retrospective, with cross sectional approach by collecting data medical records of pediatric patient with ALL in RSUP Prof. Dr. R. D. Kandou Manado then describe the incidence of diarrhea. Samples were 60.Results : The result obtained 60 patients who met the inclusion criteria, and 17 patients had diarrhea. Diarrhea in children with ALL is more common in induction phase, and the duration of diarrhea more to less than 7 days (acute diarrhea).Conclusion : From this result, it can be concluded that the incidence of diarrhea in children with Acute Lymphoblastic Leukemia in Prof. DR. R. D. Kandou Hospital Manado year period 2011-2015 is low enough.Keywords : Acute Lymphoblastic Leukemia (ALL), Diarrhea, ChildABSTRAKLatar Belakang : Leukemia merupakan jenis penyakit tidak menular yang menyebabkan kematian dengan jumlah kasus yang tidak sedikit khususnya pada anak-anak. Leukemia adalah kanker anak yang paling sering. Leukemia Limfoblastik Akut (LLA) berjumlah kira-kira 75% dari semua kasus. Salah satu konsekuensi utama dari Leukemia adalah ketidakmampuan sistem imum mempertahankan tubuh dari invasi benda asing. Akibatnya infeksi atau perdarahan hebat adalah penyebab tersering kematian pada pasien leukemia. Diare merupakan salah satu infeksi yang dapat dijumpai pada anak dengan Leukemia Limfoblastik Akut. Diare pada anak dengan Leukemia Limfoblastik Akut dapat terjadi baik akibat dari Leukemia Limfoblastik Akut itu sendiri maupun akibat dari kemoterapi yang diberikan.Metode : Penelitian ini bersifat retrospektif deskriptif, dengan pendekatan potong lintang dengan cara mengumpulkan rekam medik pasien anak dengan LLA di RSUP Prof. Dr. R. D. Kandou Manado, kemudian mendeksripsikan kejadian diare.Hasil : Didapatkan 60 pasien yang memenuhi kriteria inklusi, dan 17 pasien mengalami diare. Diare pada anak dengan LLA lebih sering terjadi pada fase induksi, dan lamanya diare lebih banyak pada < 7 hari (diare akut).Kesimpulan : Angka kejadian diare pada anak dengan Leukemia Limfoblastik Akut di RSUP Prof. DR. R. D. Kandou periode tahun 2011-2015 cukup rendah.Kata Kunci : Leukemia Limfoblastik Akut (LLA), Diare, Anak